The Influence of Pure Coconut Oil Business on the Welfare of Coconut Farmers in Padang Bolak District, North Padang Lawas Regency - Gulo, Ahmad Jumadin; Lubis, Rizal P. (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
Indonesia has great potential in the coconut industry to improve regional and national economies through coconut production and its derivative products, although coconut production by small farmers is still low. With an annual production of 18.30 million tons and a market share of 30.24% of world coconut production, Indonesia is one of the largest coconut producers in the world. Coconut production is concentrated in large islands such as Sumatra, Java, and Sulawesi, with an average productivity of 11.36 tons per hectare in 2014. Pure coconut oil (Virgin Coconut Oil or VCO), which has been proven to be beneficial for health, is increasingly in demand along with the trend of natural and pure healthy foods. The community of Padang Bolak District, this great potential has not been fully utilized due to various obstacles such as technology, capital, and uneven market absorption. This study aims to identify factors (price, production, distribution, labor, technology, capital, skills, potential) that are relevant in improving the welfare of the community in Gunung Tua Baru Village, North Padang Lawas Regency. With a sample size of 134 respondents collected through questionnaires and data processing using Confirmatory Factor Analysis (CFA) and Multiple Linear Regression, the results of the CFA analysis showed that of the eight factors analyzed, there were four factors that significantly influenced the welfare of the community in Gunung Tua Baru Village, namely production, labor, capital, and technology. The results of multiple linear regression showed that these four factors significantly influenced the improvement of community welfare. Simultaneous hypothesis testing also showed that production, labor, capital, and technology positively and significantly influenced the welfare of the community in Gunung Tua Baru Village. Thus, increasing production, labor, capital, and technology is very much needed to optimize the potential of coconuts and improve the welfare of the community in Padang Bolak District.